2021
DOI: 10.1037/amp0000717
|View full text |Cite
|
Sign up to set email alerts
|

Religion and reactance to COVID-19 mitigation guidelines.

Abstract: During the current COVID-19 pandemic, religious gatherings have become intense hot spots for the spread of the virus. In this research, we focus on the religiosity of communities to examine whether religiosity helps or hinders adherence to mitigation policies such as shelter-in-place directives. Prior research makes opposing predictions as to the influence of religiosity. One stream predicts greater adherence because of rule-abiding norms and altruistic tendencies while another predicts lower adherence as a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
2
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 90 publications
6
61
2
8
Order By: Relevance
“…9,29 Most asylum seekers did not believe they were at-risk for COVID-19 disease in the camp, with reasons varying from adherence to public health measures, to special defenses including strong immunity and protection from God. One study found that religiosity correlated to decreased adherence of COVID-19 mitigation guidelines, 30 supporting our findings and suggesting that religious beliefs could play a role in COVID-19 perceptions and education. No other research discussed a belief of protection from COVID-19 due to God, marking a novel finding.…”
Section: Discussionsupporting
confidence: 90%
“…9,29 Most asylum seekers did not believe they were at-risk for COVID-19 disease in the camp, with reasons varying from adherence to public health measures, to special defenses including strong immunity and protection from God. One study found that religiosity correlated to decreased adherence of COVID-19 mitigation guidelines, 30 supporting our findings and suggesting that religious beliefs could play a role in COVID-19 perceptions and education. No other research discussed a belief of protection from COVID-19 due to God, marking a novel finding.…”
Section: Discussionsupporting
confidence: 90%
“…Although not as consistent or robust as partisanship or collectivism while controlling for relevant constructs, the results of this study generally parallel recent research findings (DeFranza et al, 2020;Jaja et al, 2020;Perry et al, 2020;Vermeer & Kregting, 2020) as well as anecdotal accounts of defiance among ardent religious bodies (BBC, 2020;Noyes, 2020;Shin, 2020). To the extent that policies are viewed as restricting one's religious freedom, opposition may remain a rampant issue (DeFranza et al, 2020;Jaja et al, 2020). However, it remains necessary to also conduct further research in efforts to better separate religious zealotry from Christian nationalism.…”
Section: Discussionsupporting
confidence: 75%
“…High prevalence of COVID-19 cases has been linked to the continued provision of in-person religious services in defiance of local or federal policies (Jaja et al, 2020;Noyes, 2020;Shin, 2020;Vermeer & Kregting, 2020). Early evidence also points to greater defiance of shelter-in-place directives among areas with greater W O R K I N G P A P E R S E R I E S religiosity (Jaja et al, 2020) as such policies may be regarded as restricting one's religious freedom to congregate (DeFranza et al, 2020). The relation between religiosity and mask-adherence, however, requires further research.…”
Section: Religion On Mask Wearingmentioning
confidence: 99%
“…This is why a global partnership between Governments, Health Systems and all Religions may support the fight against the COVID-19 pandemic, promoting interreligious/interfaith dialogue during these times. Such a dialogue would allow a more concrete support of poor communities and active engagement of minorities in order to limit the spread of the virus (40), since for some religious practitioners the imposition of restrictions, including church closures, may be linked to restrictions to adhere to the preventive measures (41). Religious institutions already played a role to defeat Ebola in west Africa (42).…”
Section: Covid-19 and Religions: Opportunitiesmentioning
confidence: 99%